Magnetic vortex oscillators. (6th October 2015) - Hrkac, Gino; Keatley, Paul S; Bryan, Matthew T; Butler, Keith
Abstract: The magnetic vortex has sparked the interest of the academic and industrial communities over the last few decades. From their discovery in the 1970s for bubble memory devices to their modern application as radio frequency oscillators, magnetic vortices have been adopted to modern telecommunication and sensor applications. Basic properties of vortex structures in the static and dynamic regime, from a theoretical and experimental point of view, are presented as well as their application in spin torque driven nano-pillar and magnetic tunnel junction devices. Single vortex excitations and phase locking phenomena of coupled oscillators are discussed with an outlook of vortex oscillators in magnetic hybrid structures with imprinted domain confinement and dynamic encryption devices.